Kompetensi Pedagogik Guru PAI Sekolah Penggerak Berbasis Pesantren di SMA Annuqayah Guluk-Guluk Sumenep - Hadits, Hadits; Sari, Desi Utari Dewi Indah; Amrullah, Amrullah (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
This research highlights the importance of PAI teacher competency in driving schools. The aim of this research is to analyze the competency of PAI teachers at driving schools at Annuqayah High School. The Driving School is part of the Merdeka curriculum in learning. This research method uses qualitative which can describe the competency of PAI teachers. The qualitative method used is descriptive by obtaining data from interviews, observation and documentation. As a result, PAI teachers become facilitators, digitalizing reflective learning to evaluation, the supporting factors are collaboration and coordination. The inhibiting factors are lack of supervision and inactive KKG.